The Influence of Social Capital on the Poverty Level of Business Actors during the Period of Natural Disasters and the COVID-19 Pandemic - Roslinawati, Roslinawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the influence of social capital on the poverty level of business actors in the Urban Forest of Palu City. This study used quantitative methods to test the theory or variables studied (social capital and poverty variables). The population of this study was business actors who are included in the poor category in the Urban Forest of Palu City with a total of 82 business actors. Determination of the sample used the census technique so that the entire population was used as samples. Data were collected by observation, questionnaires, and documentation. Then, the data were analyzed using multiple linear regression to identify the influence of social capital on the poverty variable. The results showed that social capital influences the poverty level of business actors in the Urban Forest of Palu City with a value of 8.7% while the remaining 91.3% is influenced by other variables outside this study.